Thiaspirofulvene compounds, methods of synthesis and use thereof

CN122810132APending Publication Date: 2026-09-25HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611110910.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-09-25

AI Technical Summary

Benefits of technology

[0027]本发明以二噻吩并[2,3-b:3',2'-d]噻吩、2-萘甲醛为主要构筑单元,通过Wittig反应、光环化、DMF醛基化和Knoevenagel缩合等多步反应分别以总产率为8.6%、8.4%、8.1%制得液晶分子T5-T、T6-T、T7-T。T5-T、T6-T在癸烷溶液中形成三维空间网状结构,表明T5-T和T6-T在癸烷溶剂中发生组装并形成超分子凝胶。凝胶化使T5-T和T6-T的荧光量子产率从1%和0.8%提升至12%和5.2%,荧光强度增强了12倍和6.5倍,荧光寿命由纳秒级(2.1 ns和1.7 ns),延长至微秒级(13.2 μs和12.5 μs)。通过改变T5-T和T6-T的氯仿/癸烷溶剂比例和控制其达到各向同性后的降温速率可实现对组装体的手性控制。其中,T5-T在氯仿/癸烷(v/v = 6/4)溶剂体系中显示出负信号,其glum值为-0.6 ×10-3;而在2/8时CPL信号发生反转,其glum值为+1.3 ×10-3。T6-T组装体在溶剂比3/7和7/3时分别显示相反信号(glum= +3.1 × 10−3和-2.2 ×10-3)。此外,控制T5-T和T6-T在达到各向同性后的降温速率,分别以60 ℃/min和1 ℃/min得到可在室温下稳定存在的液晶相和晶态薄膜。T5-T和T6-T在液晶相薄膜中显示出正的CPL信号,其glum值为+2.3 ×10-2和+5.1 ×10-2,而在晶态薄膜中显示负信号,其glum值为-3.6 × 10-3和-8.1 × 10-3。推测这种CPL信号反转是因为硫杂螺烯液晶分子在不同状态下具有不同的分子堆积模式。液晶分子T5-T和T6-T液晶相的glum值与组装体及晶态相比均有数量级的提升,表明有序的液晶结构更有利于增强手性光学活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122810132A_ABST
    Figure CN122810132A_ABST
Patent Text Reader

Abstract

This invention discloses a class of thiaspirene compounds, their synthesis methods, and applications, belonging to the field of organic functional materials. In a THF / H₂O mixed solvent, the fluorescence intensity of compounds T5-T, T6-T, and T7-T gradually increases with increasing water content, reaching its maximum at water contents of 70%, 80%, 90%, and 90%, respectively. T5-T and T6-T assemble in decane to form a supramolecular gel. Gelation increases the fluorescence quantum yield of T5-T and T6-T from 1% and 0.8% to 12% and 5.2%, respectively, with fluorescence intensity increasing by 12-fold and 6.5-fold, and fluorescence lifetimes extending from nanoseconds (2.1 ns and 1.7 ns) to microseconds (13.2 μs and 12.5 μs). T5-T exhibits a negative signal in a chloroform / decane (v / v=6 / 4) solvent system, with its g... lum The value is -0.6 × 10 ‑3 At 2 / 8, the CPL signal inverts, and its g lum The value is +1.3 × 10 ‑3 The T6-T assembly exhibited opposite signals at solvent ratios of 3 / 7 and 7 / 3 (g). lum =+3.1 × 10 ‑3 and -2.2 × 10 ‑3 ).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic functional materials, specifically relating to a class of thiaspirene compounds and their synthesis methods and applications. Background Technology

[0002] Based on whether heteroatoms are introduced into the molecular skeleton of helicene, it can be divided into carbon helicene and hetero helicene: the former is composed only of carbon-hydrogen skeleton (such as [7] helicene), which has excellent thermal stability and intrinsic chiral response; the latter achieves electronic structure regulation and solubility optimization by introducing heteroatoms such as nitrogen, oxygen, and sulfur (such as thiohelicene), and the coordination ability of heteroatoms can expand its application in the fields of catalysis and biosensing.

[0003] Both types of materials exhibit circularly polarized luminescence properties, but the introduction of heteroatoms often enhances molecular polarizability and improves the photoelectric response efficiency of the material. Heterohelicenes, through the heteroatom-induced asymmetric intramolecular charge distribution, significantly enhance the synergistic effect of electric and magnetic dipole moments, making g... lum The value increases by 1-2 orders of magnitude (e.g., thiaspirene g). lum Up to 10 -2 Meanwhile, the coordination ability of heteroatoms can be used to construct metal-organic hybrid systems, enabling dynamic control of CPL signals, which has greater application potential in optical anti-counterfeiting and bioimaging. Summary of the Invention

[0004] To overcome the above-mentioned technical defects, the present invention provides a class of thiaspirene compounds, their synthesis methods and applications.

[0005] Based on the above objectives, the present invention initially adopts the following technical solution:

[0006] A class of thiaspirene compounds, with the following structural formula:

[0007] , , .

[0008] The synthetic route for the above-mentioned thiaspirene compounds is as follows:

[0009] The specific preparation process is as follows:

[0010] (1) Under a protective atmosphere, compound 5 and compound 6, 9 or 14 were dissolved in methanol to obtain a substrate solution, potassium tert-butoxide was dissolved in methanol to obtain a methanol solution of potassium tert-butoxide, the methanol solution of potassium tert-butoxide was cooled to -5~5 ℃, and the substrate solution was added dropwise to the methanol solution of potassium tert-butoxide under anaerobic conditions at -5~5 ℃, and the reaction was carried out at -5~5 ℃ for 20~40 min, then allowed to return to room temperature naturally, and heated to 85~95 ℃ to complete the reaction; the reaction system was cooled to room temperature, methanol was removed by rotary evaporation, dichloromethane was extracted, the obtained organic phases were combined, washed with water, dried with anhydrous Na2SO4, filtered with filter paper, concentrated to obtain crude product, and separated by washing with methanol and centrifugation to obtain compound 5a, 6a or 7a;

[0011] (2) Under a protective atmosphere, compound 5a, 6a or 7a was dissolved in dry toluene. After stirring and dissolving, iodine and propylene oxide were added. The reaction was irradiated with a high-pressure mercury lamp until complete. The reaction was quenched by adding saturated sodium sulfite solution. The mixture was extracted with dichloromethane. The resulting organic phases were combined, washed with water, dried with anhydrous Na2SO4, filtered with filter paper, and dichloromethane was removed by rotary evaporation to obtain the crude product. Compound 5b, 6b or 7b was obtained by column chromatography.

[0012] (3) Under a protective atmosphere, anhydrous diethyl ether was added to the reaction flask, and redistilled diisopropylamine was added under an ice-water bath. After stirring evenly, n-BuLi was added dropwise while stirring continuously. The reaction was carried out under an ice-water bath for 20-40 min to obtain LDA.

[0013] Under a protective atmosphere, compounds 5b, 6b, or 7b were dissolved in anhydrous diethyl ether, cooled to -70 to -80°C, and LDA was added dropwise. The reaction was maintained at -70 to -80°C for 1 to 3 hours. DMF was then added dropwise at -70 to -80°C, and the mixture was allowed to return to room temperature until the reaction was complete. The reaction was quenched by adding methanol dropwise to the reaction system at -70 to -80°C. DMF was removed by rotary evaporation, and the mixture was extracted with dichloromethane. The resulting organic phases were combined, washed with water, dried over anhydrous Na2SO4, filtered through filter paper, and concentrated to obtain the crude product. Compounds 5c, 6c, or 7c were then separated by column chromatography.

[0014] (4) Dissolve compounds 5c, 6c or 7c, compound 19, and sodium ethoxide in a mixed solvent of ethanol and tetrahydrofuran, install a reflux condenser, and react completely at 45~55 °C. Remove the solvent by evaporation, extract with dichloromethane, combine the organic phases, wash with water, dry with anhydrous Na2SO4, filter with filter paper, remove the solvent by evaporation to obtain the crude product, and separate by column chromatography to obtain the target compounds T5-T, T6-T or T7-T.

[0015] Further, in step (1), the molar ratio of compound 6, 9 or 14, compound 5 and potassium tert-butoxide is (1.0~1.5):1:(1.5~2). In step (2), the molar ratio of compound 5a, 6a or 7a to elemental iodine and propylene oxide is 1:(1.5~2):(90~110), and the power of the high-pressure mercury lamp is 1000W. In step (3), the molar ratio of diisopropylamine and n-BuLi is (1.1~1.5):1; the molar ratio of compound 5b, 6b or 7b, lithium diisopropylamine and DMF is 1:(1.1~1.5):2. In step (4), the molar ratio of compound 5c, 6c or 7c, compound 19 and sodium ethoxide is 1:5:8, and the volume ratio of ethanol to tetrahydrofuran in the mixed solvent of ethanol and tetrahydrofuran is 3:1.

[0016] Furthermore, the preparation process of 9 is as follows:

[0017]

[0018] Compounds 7 and 8 were dissolved in acetone and reacted at 70-80 °C for 10-15 h. After cooling naturally to room temperature, the mixture was centrifuged. The solid was washed with anhydrous diethyl ether and centrifuged again to obtain compound 9. The molar ratio of compounds 7 and 8 was 1:1.

[0019] Furthermore, the preparation process of 14 is as follows:

[0020]

[0021] For details on the preparation process, please refer to: S. Fujino, M. Yamaji, H. Okamoto, et al. Systematic Investigations on Fused π-System Compounds of Seven Benzene Rings Prepared by Photocyclization of Diphenanthrylethenes[J]. Photochemical & Photobiological Sciences, 2017, 16, 925-934.

[0022] Furthermore, the preparation process of 19 is as follows:

[0023]

[0024] For detailed preparation procedures, please refer to the following reference: Y. Zhao, G. Xu, X. Guo, et al. Cooperative Assembly of An Active Layer Utilizing the Synergistic Effect of A FunctionalFullerene Triad as An Acceptor for Efficient P3HT-based PSCs[J]. Journal of Materials Chemistry A, 2015, 3, 17991-18000.

[0025] The above-mentioned thiaspirene compounds are used as liquid crystal materials or circularly polarized light-emitting materials.

[0026] The present invention has the following beneficial effects:

[0027] This invention utilizes dithiopheno[2,3-b:3',2'-d]thiophene and 2-naphthaldehyde as the main building blocks, and synthesizes liquid crystal molecules T5-T, T6-T, and T7-T in total yields of 8.6%, 8.4%, and 8.1% respectively through a multi-step reaction involving Wittig reaction, photocyclization, DMF aldehyde conversion, and Knoevenagel condensation. T5-T and T6-T form a three-dimensional network structure in decane solution, indicating that T5-T and T6-T assemble and form a supramolecular gel in decane solvent. Gel formation increases the fluorescence quantum yield of T5-T and T6-T from 1% and 0.8% to 12% and 5.2%, respectively, enhances fluorescence intensity by 12-fold and 6.5-fold, and extends fluorescence lifetime from nanoseconds (2.1 ns and 1.7 ns) to microseconds (13.2 μs and 12.5 μs). Chiral control of the assemblies can be achieved by changing the chloroform / decane solvent ratio of T5-T and T6-T and controlling the cooling rate after isotropic formation. Specifically, T5-T exhibits a negative signal in the chloroform / decane (v / v = 6 / 4) solvent system, with its g... lum The value is -0.6 × 10 -3 At 2 / 8, the CPL signal inverts, and its g lum The value is +1.3 × 10 -3 The T6-T assembly showed opposite signals at solvent ratios of 3 / 7 and 7 / 3 (g). lum = +3.1 × 10 −3 and -2.2 ×10 -3Furthermore, by controlling the cooling rates of T5-T and T6-T after achieving isotropy, 60 °C / min and 1 °C / min, respectively, stable liquid crystal phases and crystalline thin films were obtained at room temperature. T5-T and T6-T exhibited positive CPL signals in the liquid crystal phase thin films, with g... lum The value is +2.3 × 10 -2 and +5.1 ×10 -2 However, it exhibits a negative signal in crystalline thin films, and its g lum The value is -3.6 × 10 -3 and -8.1 × 10 -3 It is speculated that this CPL signal inversion is due to the different molecular packing modes of thiaspirene liquid crystal molecules in different states. The gi of the T5-T and T6-T liquid crystal phases... lum The values ​​are orders of magnitude higher than those of the assembled and crystalline states, indicating that the ordered liquid crystal structure is more conducive to enhancing chiral optical activity. Attached Figure Description

[0028] Figure 1 For compound T5-T 1 H NMR (400 MHz, CDCl3);

[0029] Figure 2 For compound T5-T 13 C NMR (100 MHz, CDCl3);

[0030] Figure 3 For compound T6-T 1 H NMR (400 MHz, CDCl3);

[0031] Figure 4 For compound T6-T 13 C NMR (100 MHz, CDCl3);

[0032] Figure 5 For compound T7-T 1 H NMR (400 MHz, CDCl3);

[0033] Figure 6 For compound T7-T 13 C NMR (100 MHz, CDCl3);

[0034] Figure 7 Phosphorescence spectra of compounds T5-T(a), T6-T(b), and T7-T(c) (77K, 2-MeTHF, [C] = 1 × 10⁻⁶) -5 M);

[0035] Figure 8 Comparative spectra of solution and solid states of compounds T5-T(a), T6-T(b), and T7-T(c) (room temperature, THF, [C] = 1 × 10⁻⁶) -5 M);

[0036] Figure 9 Fluorescence spectra of compound T5-T(a) at different THF / H2O ratios (Inset: Fluorescence intensity changes under 365 nm UV light irradiation with H2O contents of 0% and 80%) (Excitation wavelength: 360 nm, [C] = 1 × 10⁻⁶) -5 (M); (b) Relationship between fluorescence intensity and water content (inset: Tyndall effect diagram); (c) Particle size distribution at 80% water content (inset: SEM image);

[0037] Figure 10 Fluorescence spectra of compound T6-T(a) at different THF / H2O ratios (Inset: Fluorescence intensity changes under 365 nm UV light irradiation with H2O contents of 0% and 90% respectively) (Excitation wavelength: 360 nm, [C] = 1 × 10⁻⁶) -5 (M); (b) Relationship between fluorescence intensity and water content (inset: Tyndall effect diagram); (c) Particle size distribution at 90% water content (inset: SEM image);

[0038] Figure 11 Fluorescence spectra of compound T7-T(a) at different THF / H2O ratios (Inset: Fluorescence intensity changes under 365 nm UV light irradiation with H2O contents of 0% and 90% respectively) (Excitation wavelength: 360 nm, [C] = 1 × 10⁻⁶) -5 (M); (b) Relationship between fluorescence intensity and water content (inset: Tyndall effect diagram) (c) Particle size distribution at 90% water content (inset: SEM image)

[0039] Figure 12 Normalized fluorescence spectra of compounds T5-T(a), T6-T(b), and T7-T(c) in different polar solvents (room temperature, [C] = 1 × 10⁻⁶). -5 M, λ ex = 365 nm);

[0040] Figure 13 The diagram shows the state of compound T7-T in different solvents;

[0041] Figure 14 SEM images of the gels of compounds T5-T(a) and T6-T(b) (inset: gel photographs);

[0042] Figure 15SEM images of compound T7-T in (a) decane and (b) methylcyclohexane;

[0043] Figure 16 The fluorescence spectra of compounds T5-T(a) and T6-T(b) in monomer and gel states are shown.

[0044] Figure 17 The lifetime diagrams are shown for the monomers (a) and (b) and gel state (c) and (d) of compounds T5-T and T6-T.

[0045] Figure 18 TGA curves for compounds T5-T(a), T6-T(b), and T7-T(c);

[0046] Figure 19 The DSC curves for compounds T5-T(a), T6-T(b), and T7-T(c) are shown.

[0047] Figure 20 POM images of compound T5-T at (a) 60 ℃, (b) 105 ℃, and (c) 80 ℃;

[0048] Figure 21 POM images of compound T6-T at (a) 63 ℃, (b) 110 ℃, and (c) 85 ℃;

[0049] Figure 22 POM images of compound T7-T at (a) 70 ℃, (b) 140 ℃, and (c) 95 ℃;

[0050] Figure 23 CD spectra of compounds T5-T(a), T6-T(b), and T7-T(c)

[0051] Figure 24 CPL spectra of the assemblies of compounds T5-T(a) and T6-T(b);

[0052] Figure 25 The CD spectra of compounds T5-T(a), T6-T(b), and T7-T(c) are shown.

[0053] Figure 26 CPL spectra of compounds T5-T(a) and T6-T(b) at different cooling rates. Detailed Implementation

[0054] The present invention will be further illustrated below with specific examples. These embodiments should be understood as illustrative only and not as limiting the scope of protection of the present invention. After reading the description of the present invention, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent changes and modifications also fall within the scope defined by the claims of the present invention.

[0055] Example 1

[0056] (1) Synthesis of compound 9

[0057]

[0058] Compounds 7 (1.0641 g, 4.05 mmol, 1.0 eq), 8 (896.9 mg, 4.05 mmol, 1.0 eq), and 20 mL of acetone were added to a 50 mL Schlenk flask. The mixture was heated to 75 °C in an oil bath and maintained at 75 °C for 12 h. After cooling to room temperature, the supernatant and solid were separated by centrifugation. The solid was washed with anhydrous diethyl ether (3 × 5 mL) and centrifuged again to give a white solid compound 9: 1.6669 g, yield: 85%.

[0059] (2) Synthesis of compound 11

[0060]

[0061] Compounds 10 (2.5 mL, 1.019 g / mL, 21.20 mmol, 1.0 eq) and 6 (9.89 g, 25.44 mmol, 1.2 eq) were added to a 100 mL round-bottom flask, followed by 100 mL of chloroform. After stirring and dissolving for 10 min, 10 mL of 50 wt% KOH solution was slowly added through a constant-pressure dropping funnel. The mixture was then heated to 65 °C in an oil bath and maintained at 65 °C for 1 h.

[0062] The reaction system was cooled to room temperature, and the aqueous phase was extracted with DCM (3 × 30 mL). The resulting organic phases were combined and washed with water (3 × 20 mL). Anhydrous Na₂SO₄ was added to the organic phase as a drying agent to remove water. Na₂SO₄ and the organic phase were then separated using filter paper. The crude product (4.2136 g) was obtained by vacuum extraction under reduced pressure. Column chromatography (300-400 mesh silica gel, wet loading, mobile phase: PE) yielded a white solid (11 g) of 3.7727 g, with a yield of 92%.

[0063] (3) Synthesis of compound 12

[0064]

[0065] Compound 11 (60 mg, 0.30 mmol, 1.0 eq) and 15 mL of cyclohexane were added to the light tube and stirred until dissolved. Then, elemental iodine (4 mg, 0.01 mmol, 0.05 eq) and a large excess of propylene oxide (approximately 100 eq) were added. The light tube was sealed, argon gas was introduced to remove oxygen for 10 min, and then the tube was irradiated with a high-pressure mercury lamp (1000 W, 10.0 A) for 12 h.

[0066] Cyclohexane was removed under reduced pressure and vacuum, then the reaction was quenched with saturated sodium thiosulfate solution. The aqueous phase was extracted with DCM (3 × 40 mL), and the resulting organic phases were combined and washed with water (3 × 30 mL). Anhydrous Na₂SO₄ was added to the organic phase as a drying agent to remove water. The Na₂SO₄ and organic phases were then separated by filter paper. The crude product was concentrated under reduced pressure to obtain 67.3 mg. Column chromatography (300-400 mesh silica gel, wet loading, mobile phase: PE) yielded 12 mg of white solid, 53.8 mg, with a yield of 89%.

[0067] (4) Synthesis of compound 13

[0068]

[0069] Compound 12 (1.6149 g, 8.40 mmol, 1.0 eq), NBS (1.72 g, 9.66 mmol, 1.2 eq), and benzoyl peroxide (BPO, 101.7 mg, 0.42 mmol, 0.05 eq) were added sequentially to a 50 mL Schlenk flask. The mixture was dried under vacuum for 0.5 h, with rapid evacuation three times during the process. 25 mL of carbon tetrachloride was added under argon protection, and the mixture was heated to 80 °C in an oil bath and maintained at 80 °C for 3 h.

[0070] After natural cooling to room temperature, carbon tetrachloride was removed under reduced pressure. The aqueous phase was extracted with DCM (3 × 40 mL). The resulting organic phases were combined and washed with water (3 × 30 mL). Anhydrous Na₂SO₄ was added to the organic phase as a drying agent to remove water. The Na₂SO₄ and organic phases were then separated using filter paper. DCM was removed under reduced pressure to obtain a crude product of 2.3045 g. Column chromatography (300-400 mesh silica gel, dry loading, mobile phase: PE) yielded a pale yellow solid of 13 g: 1.2302 g, with a yield of 54%.

[0071] (5) Synthesis of compound 14

[0072]

[0073] Compounds 7 (132.0 mg, 0.50 mmol, 1.0 eq), 8 (137.2 mg, 0.50 mmol, 1.0 eq), and 20 mL of acetone were added to a 50 mL Schlenk flask. The mixture was heated to 75 °C, then heated to 75 °C in an oil bath, and maintained at 75 °C for 12 h. After natural cooling to room temperature, the supernatant and solid were separated by centrifugation. The solid was washed with anhydrous diethyl ether (3 × 7 mL) to obtain a white solid of 14:231.4 mg, yield: 86%.

[0074] (6) Synthesis of compound 16

[0075]

[0076] Compound 15 (1.5003 g, 8.14 mmol, 1.0 eq), 1-bromooctane (8.0 mL, 1.18 g / mL, 48.87 mmol, 6.0 eq), potassium carbonate (6.7561 g, 48.87 mmol, 6.0 eq), and 30 mL of dry DMF were added to a 100 mL round-bottom flask. The mixture was heated to 80 °C in an oil bath and maintained at 80 °C for 12 h.

[0077] The reaction system was cooled to room temperature, and DMF was removed under vacuum. The aqueous phase was extracted with ethyl acetate (3 × 50 mL). The resulting organic phases were combined and washed with water (3 × 40 mL). Anhydrous Na₂SO₄ was added to the organic phase as a drying agent to remove water. The Na₂SO₄ and organic phases were then separated using filter paper. The crude product was concentrated under vacuum to obtain 4.9671 g. The product was then subjected to column chromatography (300-400 mesh silica gel, dry loading, mobile phase: V). PE :V EA = 50:1) to obtain 16:3.8164 g, yield: 90%.

[0078] (7) Synthesis of compound 17

[0079]

[0080] Compound 16 (5 g, 9.60 mmol, 1.0 eq) and 30 mL of dry THF were added to a 100 mL round-bottom flask. The mixture was cooled to 0 °C in an ice-water bath, and lithium aluminum hydride (LAH, 6 mL, 14.40 mmol, 2.5 M in THF, 1.5 eq) was added dropwise. The mixture was then slowly restored to room temperature for 2 h. The reaction was monitored by TLC during the reaction. After the reaction was complete, 10 mL of methanol and water were added to quench the reaction. The mixture was extracted with ethyl acetate (3 × 40 mL), and all organic phases were combined and washed with water (3 × 40 mL). Anhydrous Na₂SO₄ was used as a drying agent. The organic phase and Na₂SO₄ were separated by filter paper. DCM was removed under reduced pressure to obtain a crude product of 4.9362 g. The product was then subjected to column chromatography (300-400 mesh silica gel, dry loading, mobile phase V). PE :V EA Compound 17 was isolated by a ratio of 5:1, yielding 4.0422 g of 4.0422 g, with a yield of 86%.

[0081] (8) Synthesis of compound 18

[0082]

[0083] Compound 17 (50.0 mg, 0.10 mmol, 1.0 eq) and triphenylphosphine (PPh3, 31.9 mg, 0.12 mmol, 1.2 eq) were added sequentially to a 50 mL Schlenk flask. The mixture was dried under vacuum for approximately 0.5 h. Then, 10 mL of THF was added under argon protection, and the mixture was stirred for 20 min. An anaerobic reaction was then performed again, with NBS (19.9 mg, 0.11 mmol, 1.1 eq) added to the 50 mL Schlenk flask. The reaction was carried out in the dark for 3 h.

[0084] The solvent was removed under reduced pressure and vacuum, followed by extraction with DCM (3 × 30 mL). The combined organic phases were collected and washed with water (3 × 20 mL). Anhydrous sodium sulfate was used as a drying agent, and the organic phase and Na₂SO₄ were separated using filter paper. The crude product (142.1 mg) was obtained by removing DCM under reduced pressure and vacuum. The product was then subjected to column chromatography (300-400 mesh silica gel, dry loading, mobile phase V). PE :V EA = 10:1) to separate a yellow solid of 18:47.6 mg, yield: 85%.

[0085] (9) Synthesis of compound 19

[0086]

[0087] Compound 18 (935.0 mg, 1.68 mmol, 1.0 eq), trimethylcyanosilane (TMSCN, 0.3 mL, 0.793 g / mL, 2.52 mmol, 1.5 eq), tetrabutylammonium fluoride (TBAF, 2.8 mL, 0.953 g / mL, 10.09 mmol, 6.0 eq) and 20 mL of acetonitrile were added sequentially to a 100 mL round-bottom flask, and the reaction was carried out at room temperature for 3 h.

[0088] Acetonitrile was removed under reduced pressure and vacuum, followed by extraction with DCM (3 × 40 mL). The combined organic phases were collected and washed with water (3 × 30 mL). Anhydrous Na₂SO₄ was used as a drying agent, and the organic phase and Na₂SO₄ were separated using filter paper. DCM was removed under reduced pressure and vacuum to obtain a crude product of 1.0237 g. The product was then subjected to column chromatography (neutral alumina, mobile phase: V). PE :V EA = 9:1) gave a white solid of 19:548.6 mg, yield: 65%.

[0089] (17) Synthesis of compound 5a

[0090]

[0091] Compounds 5 (300.0 mg, 1.34 mmol, 1.0 eq) and 6 (638.4 mg, 1.60 mmol, 1.1 eq) were added sequentially to a 100 mL Schlenk flask, and potassium tert-butoxide (225.3 mg, 2.00 mmol, 1.5 eq) was added to a 250 mL Schlenk flask. The reaction system was dried under vacuum for 1 h, with rapid gas exchange at least three times during this period. 40 mL and 150 mL of methanol were added respectively under argon protection. The reaction system in the 250 mL Schlenk flask was cooled to 0 °C, and the solution from the 100 mL Schlenk flask was slowly added dropwise to the 250 mL Schlenk flask under anaerobic conditions at 0 °C. The reaction was initially maintained at 0 °C for 30 min, then slowly restored to room temperature, and finally heated to 90 °C in an oil bath and maintained at 90 °C for 18 h.

[0092] After cooling the reaction system to room temperature, methanol was removed under reduced pressure and vacuum. The mixture was then extracted with DCM (3 × 50 mL). The resulting organic phases were combined and washed with water (3 × 30 mL). Anhydrous Na₂SO₄ was used as a drying agent, and the organic phases were separated using filter paper. The crude product was concentrated under reduced pressure to obtain 410.2 mg. After washing with methanol and centrifugation (6 × 10 mL), a pale yellow solid 5a was obtained: 352.3 mg, yield: 88%. MP: 149.5–150.3 °C. 1H NMR (400 MHz, CDCl3) (for a mixture of cis andtrans isomers of 5a) δ 7.50 (d, J = 7.6 Hz), 7.41 (t, J = 4.2 Hz), 7.39-7.35(m), 7.33 (s), 7.29 (d, J = 9.5 Hz), 6.94 (d, J = 16.0 Hz); the ratio ofintegral areas of the peaks is 2.0 : 1.9 : 2.8 : 1.0 : 1.8 :1.0. 13 C NMR (125MHz, CDCl3) δ 145.71, 138.82, 138.68, 138.45, 137.87, 137.23, 136.85, 129.17,129.07, 128.90, 128.83, 128.34, 127.95, 127.92, 127.90, 127.77, 126.46,124.19, 122.44, 119.87, 118.94, 117.91. HRMS (EI-FT) m / z [M] + calcd for[C 16 H 10 S3] 297.9945; found 297.9937.

[0093] (18) Synthesis of compound 5b

[0094]

[0095] Compound 5a (20 mg, 0.06 mmol, 1.0 eq) and 15 mL of dry toluene were first added to the light tube and stirred until dissolved. Then, elemental iodine (25 mg, 0.10 mmol, 1.5 eq) and a large excess of propylene oxide (approximately 100 eq) were added. Finally, the light tube was sealed, argon gas was introduced to remove oxygen for 10 min, and the tube was irradiated with a high-pressure mercury lamp (1000 W, 6A) for 10 h.

[0096] The reaction system was quenched with saturated sodium sulfite solution, extracted with DCM (3 × 40 mL), and the resulting organic phases were combined and washed with water (3 × 30 mL). Anhydrous Na₂SO₄ was used as a drying agent, and the organic phases were separated with filter paper. DCM was removed under reduced pressure to obtain a crude product of 77.2 mg. Column chromatography (200-300 mesh silica gel, dry loading, mobile phase: PE) was used to separate the product into a pale yellow solid 5b of 70.3 mg, yield: 78%. MP: 148.7-149.8 ℃. 1 H NMR (400 MHz, CDCl3) δ 9.06 (d,J = 8.4 Hz, 1H), 8.15 (d, J = 5.4 Hz, 1H), 8.02 (d, J = 8.1 Hz, 1H), 7.87 (d,J = 8.7 Hz, 1H), 7.79 (d, J = 8.7 Hz, 1H), 7.77-7.70 (m, 1H), 7.63-7.58 (m,1H), 7.57 (d, J = 5.4 Hz, 1H). 13 C NMR (125 MHz, CDCl3) δ 140.87, 140.65,139.75, 139.14, 134.18, 131.83, 129.30, 129.22, 128.98, 127.01, 126.10,125.38, 125.15, 125.11, 121.94, 121.46. HRMS (EI-FT) m / z [M] + calcd for[C 16 H8S3] 295.9788; found 295.9781.

[0097] (19) Synthesis of compound 5c

[0098]

[0099] Preparation of lithium diisopropylamino (LDA): Take a 10 mL Schlenk flask, evacuate and dry for about 0.5 h, with rapid gas exchange three times during the process. Add 2 mL of anhydrous diethyl ether under argon protection, then cool to 0 °C in an ice-water bath. Add redistilled diisopropylamine (0.07 mL, 0.48 mmol, 1.2 eq), stir well, and then add n-BuLi dropwise under argon protection (1.32 min hexane, 0.3 mL, 0.40 mmol, 1.0 eq) with constant stirring. React at 0 °C for 30 min.

[0100] First, 5b (74.3 mg, 0.25 mmol, 1.0 eq) was added to a 50 mL Schlenk flask, and then the mixture was dried under vacuum for about 1.0 h, with rapid evacuation at least three times during this period. Then, 15 mL of anhydrous diethyl ether was added under argon protection. The temperature was lowered to -78 °C, and homemade LDA (1.3 eq in Et₂O, 2 mL) was slowly added dropwise under anaerobic conditions at -78 °C, maintaining the reaction at -78 °C for 2 h. Then, under argon protection, DMF (0.1 mL, 0.50 mmol, 2.0 eq) was added dropwise at -78 °C, and the reaction was slowly restored to room temperature for 12 h.

[0101] The reaction was quenched by adding 2 mL of methanol dropwise to the reaction system at -78 ℃. THF was removed under reduced pressure and vacuum. Extraction was performed using DCM (3 × 40 mL). The resulting organic phases were combined and washed with water (3 × 30 mL). Anhydrous Na₂SO₄ was used as a drying agent. The organic phase and Na₂SO₄ were separated using filter paper. DCM was removed under reduced pressure and vacuum to obtain the crude product: 134.9 mg. The product was then subjected to column chromatography (200-300 mesh silica gel, dry loading, mobile phase: V). PE :V DCM = 5:1) to isolate a pale yellow solid compound 5c: 61.7 mg, yield: 76%. MP: 235.8-236.7 ℃. 1 H NMR (500 MHz, CDCl3) δ 10.06 (s, 1H), 8.88 (d, J = 8.4 Hz,1H), 8.66 (s, 1H), 8.04 (d, J = 8.1 Hz, 1H), 7.87 (d, J = 8.7 Hz, 1H), 7.82(d, J = 8.7 Hz, 1H), 7.81-7.76 (m, 1H), 7.67-7.61 (m, 1H). 13 C NMR (125 MHz, CDCl3) δ 183.06, 149.35, 145.45, 141.61, 141.26, 139.07, 134.03, 131.90,130.33, 129.31, 129.11, 128.88, 126.57, 125.83, 125.75, 124.55, 121.40. HRMS(EI-FT) m / z [M] + calcd for [C 16 H8S3O] 323.9737; found 323.9737.

[0102] (20) Synthesis of compound T5-T

[0103] Compound 5c (15.2 mg, 0.04 mmol, 1.0 eq), 19 (120.5 mg, 0.23 mmol, 5.0 eq), sodium ethoxide (25.6 mg, 0.37 mmol, 8.0 eq), 15 mL of ethanol and 5 mL of tetrahydrofuran were added sequentially to a 50 mL round-bottom flask. A reflux condenser was installed, and the mixture was heated to 50 °C in an oil bath and maintained at 50 °C for 1 hour.

[0104] Solvent was removed under reduced pressure and extracted with DCM (3 × 30 mL). All organic phases were combined and washed with water (3 × 20 mL). Anhydrous Na₂SO₄ was used as a drying agent. The organic phase and Na₂SO₄ were separated by filter paper. DCM was removed under reduced pressure to obtain crude product: 121.3 mg. The product was then subjected to column chromatography (200-300 mesh silica gel, dry loading, mobile phase: V). PE :V DCM = 2:1) to separate a yellow-green solid T5-T: 23.2 mg, yield: 62%. MP: 89.5-90.1 ℃. 1 H NMR and 13 C NMR spectra as follows Figure 1 , Figure 2 As shown. 1 H NMR (400 MHz, CDCl3) δ 8.79 (d, J = 8.4 Hz, 1H), 8.18 (s, 1H), 8.02 (d, J= 8.1 Hz, 1H), 7.85-7.78 (m, 2H), 7.74 (t, J = 7.7 Hz, 1H), 7.63 (d, J = 8.1Hz, 2H), 6.67 (s, 2H), 4.06 (t, J = 6.6 Hz, 2H), 3.98 (t, J = 6.6 Hz, 4H), 1.80 (m, 6H), 1.43 (m, 6H), 1.33-1.25 (m, 24H), 0.87 (m, 9H). 13C NMR (100MHz, CDCl3) δ 154.44, 145.65, 141.10, 140.87, 139.67, 138.69, 137.90, 137.78,133.67, 131.81, 129.15, 129.08, 128.92, 127.39, 126.64, 126.47, 125.66,125.56, 124.59, 121.36, 120.21, 110.14, 107.37, 73.73, 69.36, 32.07, 31.94,30.53, 29.85, 29.72, 29.56, 29.48, 29.45, 29.41, 26.27, 26.17, 22.87, 22.80,14.28, 14.24. HRMS (ESI-FT) m / z [M+H] + calcd for [C 49 H 62 O3NS3] 808.3847; found808.3881.

[0105] (21) Synthesis of compound 6a

[0106]

[0107] The experimental procedure was the same as for compound 5a, yielding a crude product of 165.5 mg. The crude product was washed with methanol and centrifuged (6 × 10 mL) to separate a pale yellow solid, compound 6a, of 129.7 mg (yield: 87%). MP: 208.5–209.9 °C. 1 H NMR (500MHz, CDCl3) δ 7.92 (s, 1H), 7.89-7.80 (m, 3H), 7.53-7.48 (m, 3H), 7.35 (d, J= 5.2 Hz, 1H), 7.31-7.26 (m, 2H), 6.83 (d, J = 11.9 Hz, 1H), 6.76 (d, J =11.9 Hz, 1H). 13C NMR (125 MHz, CDCl3) δ 142.68, 139.81, 138.73, 138.49,137.24, 135.17, 133.65, 133.06, 129.02, 128.40, 128.28, 128.21, 127.93,127.78, 126.91, 126.36, 126.35, 124.49, 120.10, 118.97. HRMS (DART-FT) m / z [M+H] + calcd for [C 20 H 13 S3] 349.0174; found 349.0176.

[0108] (22) Synthesis of compound 6b

[0109]

[0110] The experimental procedure was the same as for compound 5b, yielding a crude product of 35.8 mg. The crude product was then subjected to column chromatography (200-300 mesh silica gel, dry loading, mobile phase: V). PE :V DCM = 5:1) to separate a pale yellow solid 6b: 21.4 mg, yield: 67%. MP: 220.3-221.4 ℃. 1 H NMR (400 MHz, CDCl3) δ 8.61 (d, J = 8.3 Hz, 1H), 8.01 (d, J= 7.9 Hz, 1H), 7.98 (d, J = 8.4 Hz, 1H), 7.87 (m, 2H), 7.80 (d, J = 8.3 Hz, 1H), 7.68-7.61 (m, 1H), 7.52-7.45 (m, 1H), 7.21 (d, J = 5.3 Hz, 1H), 6.72 (d,J = 5.3 Hz, 1H). 13 C NMR (125 MHz, CDCl3) δ 143.19, 141.69, 140.47, 138.48,135.75, 132.83, 130.58, 129.52, 129.48, 127.56, 127.36, 126.86, 126.84,126.81, 126.60, 125.47, 125.17, 124.69, 124.55, 121.61. HRMS (DART-FT) m / z [M+H] +calcd for [C 20 H 11 S3] 347.0017; found 347.0019.

[0111] (23) Synthesis of compound 6c

[0112]

[0113] The experimental procedure was the same as for compound 5c, yielding a crude product of 155.0 mg. The crude product was then subjected to column chromatography (200-300 mesh silica gel, dry loading, mobile phase: V). PE :V DCM = 4:1) to separate a pale yellow solid 6c: 96.8 mg, yield: 75%. MP: 219.9-221.3 ℃. 1 H NMR (500 MHz, CDCl3) δ 9.69 (s, 1H), 8.52 (d, J = 8.2 Hz,1H), 8.07 (d, J = 7.9 Hz, 1H), 8.02 (d, J = 8.4 Hz, 1H), 7.95-7.89 (m, 2H),7.86 (d, J = 8.4 Hz, 1H), 7.70 (t, J = 7.5 Hz, 1H), 7.52 (t, J = 7.6 Hz, 1H), 7.35 (s, 1H). 13 C NMR (125 MHz, CDCl3) δ 182.26, 148.24, 143.98, 143.32,142.64, 140.74, 136.18, 134.22, 132.95, 130.74, 129.12, 129.01, 128.06,127.16, 126.94, 126.91, 126.87, 126.62, 125.54, 125.26, 121.71. HRMS (DART-FT) m / z [M+H] + calcd for [C 21 H 11 OS3] 374.9967; found 374.9968.

[0114] (24) Synthesis of compound T6-T

[0115]

[0116] The experimental procedure was the same as for compound T5-T, yielding a crude product of 231.2 mg. The product was then subjected to column chromatography (200-300 mesh silica gel, dry loading, mobile phase: V). PE :V DCM = 4:1) to separate a pale yellow solid T6-T: 80.3 mg, yield: 72%. MP: 82.2-83.5 ℃. 1 H NMR and 13 C NMR spectra as follows Figure 3 , Figure 4 As shown. 1 H NMR (400 MHz, CDCl3) δ 8.46 (d, J =8.3 Hz, 1H), 8.06 (d, J = 7.8 Hz, 1H), 7.97 (d, J = 8.4 Hz, 1H), 7.93-7.85(m, 2H), 7.82 (d, J = 8.4 Hz, 1H), 7.71 (t, J = 7.4 Hz, 1H), 7.51 (t, J = 7.5Hz, 1H), 7.21 (s, 1H), 6.83 (s, 1H), 6.59 (s, 2H), 4.05 (t, J = 6.5 Hz, 2H), 3.96 (t, J = 6.5 Hz, 4H), 1.80 (dd, J = 13.7, 7.2 Hz, 6H), 1.45 (t, J = 7.5Hz, 6H), 1.35-1.25 (m, 24H), 0.92-0.85 (m, 9H). 13C NMR (100 MHz, CDCl3) δ154.40, 144.86, 143.31, 141.92, 139.66, 138.73, 138.32, 137.11, 135.11,132.91, 130.82, 130.67, 129.18, 129.14, 127.94, 127.14, 127.05, 126.89,126.82, 126.65, 126.52, 125.36, 125.03, 121.66, 120.32, 109.18, 107.44,75.36, 73.72, 69.35, 67.86, 33.20, 32.07, 31.95, 30.53, 29.84, 29.73, 29.56,29.50, 29.46, 29.41, 26.28, 26.19, 26.03, 22.87, 22.80, 21.10, 14.28, 14.24.HRMS (AP-MALDI-FT) m / z [M] + calcd for [C 53 H 63 O3NS3] 857.3965; found 857.3969.

[0117] (25) Synthesis of compound 7a

[0118]

[0119] The experimental procedure was the same as for compound 5a, yielding a crude product of 131.4 mg. The product was then washed with methanol (6 × 10 mL) and centrifuged to obtain a pale yellow solid 7a of 60.5 mg, yield: 85%. MP: 198.6–199.4 °C. 1H NMR (500 MHz,CDCl3) (for a mixture of cis and trans isomers of 7a) δ 8.80 (s), 8.75 (d, J= 8.2 Hz), 8.70 (s), 8.63 (d, J = 9.2 Hz), 7.93-7.88 (m), 7.87 (s), 7.79 (d,J = 18.2 Hz), 7.73 (s), 7.69 (t, J = 7.6 Hz), 7.65-7.59 (m), 7.48 (s), 7.45(s), 7.42 (d, J = 5.1 Hz), 7.39-7.37 (m), 7.34 (d, J = 6.6 Hz), 7.28 (d, J =5.2 Hz), 7.20 (s), 7.17 (s), 6.89 (d, J = 11.9 Hz), 6.85 (d, J = 11.9 Hz);the ratio of integral areas of the peaks is 0.6 : 1.3 : 1.3 : 0.6 : 2.9 : 0.8: 2.4 : 2.4 : 1.4 : 2.9 : 0.6 : 0.6 : 1.2 : 2.5 : 1.1 : 0.6 : 0.7 : 0.6 : 0.6: 0.6. 13 C NMR (125 MHz, CDCl3) δ 145.79, 142.68, 139.82, 138.86, 138.75,138.68, 138.52, 138.43, 138.00, 137.18, 135.35, 135.03, 132.48, 132.32,131.81, 131.68, 130.69, 130.52, 130.37, 130.30, 129.19, 129.17, 129.06,128.82, 128.75, 128.68, 127.96, 127.78, 127.44, 127.42, 127.20, 126.90,126.88, 126.86, 126.82, 126.79, 126.74, 124.67, 123.94, 123.38, 122.89,122.88, 122.79, 121.66, 120.30, 118.97, 118.95, 118.09. HRMS (ESI-FT) m / z [M+H]+ calcd for [C 24 H 15 S3] 399.0291; found 399.0332.

[0120] (26) Synthesis of compound 7b

[0121]

[0122] The experimental procedure was the same as for compound 5b, yielding a crude product of 36.6 mg. Separation by column chromatography (200-300 mesh silica gel, dry loading, mobile phase: n-hexane) yielded a pale yellow solid 7b of 10.2 mg, yield: 68%. MP: 281.3-282.5 ℃. 1 HNMR (500 MHz, CDCl3) δ 8.10 (d, J = 3.4 Hz, 1H), 8.08 (d, J = 3.3 Hz, 1H), 8.06 (d, J = 8.5 Hz, 1H), 8.01 (d, J = 7.9 Hz, 2H), 7.96-7.93 (m, 2H), 7.92(d, J = 8.1 Hz, 1H), 7.29 (m, 1H), 6.91-6.86 (m, 1H), 6.62 (d, J = 5.3 Hz, 1H), 5.16 (d, J = 5.3 Hz, 1H). 13 C NMR (125 MHz, CDCl3) δ 142.59, 140.55,139.15, 136.88, 136.11, 132.20, 131.81, 131.75, 131.01, 129.98, 128.04,127.76, 127.33, 127.13, 126.43, 126.40, 126.14, 126.13, 125.43, 125.03,124.36, 124.22, 121.74, 120.80. HRMS (EI-FT) m / z [M] + calcd for [C 24 H 12 S3]396.0101; found 396.0096.

[0123] (27) Synthesis of compound 7c

[0124]

[0125] The preparation steps for lithium diisopropylamino (LDA) are the same as those for compound 5c.

[0126] Compound 7b (95 mg, 0.24 mmol, 1.0 eq) was added to a 25 mL Schlenk flask and dried under vacuum for approximately 1.0 h, with rapid evacuation at least three times during this period. Then, 10 mL of tetrahydrofuran was added under argon protection. The temperature was lowered to -78 °C, and under argon protection and anaerobic conditions, 1.3 eq in Et₂O (4 mL) was slowly added dropwise, maintaining the reaction at -78 °C for 2 h. Under anaerobic conditions, DMF (0.1 mL, 0.48 mmol, 2.0 eq) was added dropwise at -78 °C, and finally, the mixture was slowly restored to room temperature for 12 h.

[0127] The reaction was quenched by adding 2 mL of methanol at -78 ℃, and THF was removed under reduced pressure. Extraction was performed using DCM (3 × 40 mL). The resulting organic phases were combined, washed with water (3 × 30 mL), and separated from the organic phase and Na2SO4 using anhydrous Na2SO4 as a drying agent. DCM was removed under reduced pressure to obtain a crude product of 35.8 mg. The product was then subjected to column chromatography (200-300 mesh silica gel, dry loading, mobile phase: V). PE / V DCM = 5 : 1) to separate a pale yellow solid 7c: 69.3 mg, yield: 69%. MP: 281.3-282.1 ℃. 1 H NMR (400 MHz, CDCl3) δ 9.18 (s, 1H), 8.13-8.04 (m, 4H), 8.03-7.97(m, 3H), 7.95 (dd, J = 8.4, 1.1 Hz, 1H), 7.29 (t, J = 6.9 Hz, 1H), 6.88 (t, J= 7.6 Hz, 1H), 5.68 (s, 1H). 13 C NMR (125 MHz, CDCl3) δ 182.89, 146.63,143.84, 142.84, 140.30, 140.19, 135.60, 132.38, 132.07, 131.94, 130.69,130.47, 129.20, 127.94, 127.78, 127.64, 127.08, 126.67, 126.62, 126.01,125.69, 125.02, 124.11, 121.86. HRMS (ESI-FT) m / z [M+H] +calcd for [C 25 H 13 S3O]425.0084; found 425.0121.

[0128] (28) Synthesis of compound T7-T

[0129]

[0130] The experimental procedure was the same as for compound T5-T, yielding a crude product of 36.7 mg. The product was then subjected to column chromatography (200-300 mesh silica gel, dry loading, mobile phase: V). PE / V DCM = 1 :1) to separate a pale yellow solid T7-T: 16.1 mg, yield: 76%. MP: 136.7-137.6 ℃. 1 H NMR and 13 C NMR spectra as follows Figure 5 , Figure 6 As shown. 1 H NMR (400 MHz, CDCl3) δ 8.04 (m,8H), 7.31 (t, J = 7.4 Hz, 1H), 6.86 (t, J = 7.8 Hz, 1H), 6.69 (s, 1H), 6.45(s, 2H), 5.19 (s, 1H), 4.01 (t, J = 6.6 Hz, 4H), 3.90 (t, J = 6.6 Hz, 2H), 1.79 (dd, J = 25.4, 7.5 Hz, 6H), 1.50 (dd, J = 14.1, 6.7 Hz, 6H), 1.33-1.26(m, 24H), 0.89 (m, 9H). 13C NMR (100 MHz, CDCl3) δ 154.16, 152.94, 142.77,138.83, 137.91, 136.97, 135.42, 132.27, 131.97, 131.83, 130.79, 129.29,127.96, 127.73, 127.52, 127.05, 126.59, 126.53, 126.47, 126.30, 126.04,125.51, 125.19, 124.75, 124.07, 121.80, 108.67, 108.11, 107.64, 73.70, 73.63,69.34, 69.31, 61.11, 32.07, 32.04, 31.97, 31.95, 30.50, 29.71, 29.66, 29.54,29.49, 29.44, 29.41, 26.26, 26.22, 26.16, 22.86, 22.80, 14.56, 14.27, 14.24.HRMS (ESI-FT) m / z [M+H] + calcd for [C 57 H 66 O3NS3] 908.4160; found 908.4208.

[0131] I. Phosphorescence Spectroscopic Characterization and Discussion of Results

[0132] Instrument used: Steady-state-transient fluorescence spectrometer (Edinburgh FLS-1000)

[0133] Solution preparation: 1. Accurately weigh compounds T5-T, T6-T, and T7-T, and place them separately into 5 mL brown volumetric flasks. Prepare solutions with spectrally pure 2-methyltetrahydrofuran to a concentration of 1×10⁻⁶. -3 1. Use a mol / L standard solution as the stock solution; 2. Take 30 µL of the above stock solution using a microsyringe and dilute it to prepare a 1×10⁻⁶ solution. -5 The test solution is mol / L.

[0134] Depend on Figure 7It was found that compounds T5-T, T6-T, and T7-T exhibited similar phosphorescence emission behaviors. The emission peak positions of compound T5-T were 497, 536, 579, and 640 nm, respectively; those of compound T6-T were 498, 530, 575, and 636 nm, respectively; and those of compound T7-T were 518, 576, and 632 nm, respectively. The phosphorescence lifetime (77K, 2-MeTHF, [C] = 1 × 10⁻⁶) was selected for testing. -5 (M) It was found that the phosphorescence lifetime gradually increased with increasing conjugation, reaching 172.9 μs, 128.1 ms, and 176.4 ms, respectively. Thioheshelicene liquid crystal molecules exhibit a significant heavy atom effect due to the presence of sulfur atoms. In the frozen state, nonradiative transitions are suppressed, and radiative transitions of triplet excitons become the main decay pathway. Simultaneously, the heavy atom effect enhances intramolecular spin-orbit coupling, thereby promoting intersystem crossing from excited singlet to excited triplet states, extending the phosphorescence lifetime to a longer duration than that of carbon helicene liquid crystal molecules.

[0135] II. Fluorescence Spectroscopy Characterization and Discussion of Results

[0136] Instrument used: Steady-state-transient fluorescence spectrometer (Edinburgh FLS-1000)

[0137] Solution preparation: 1. Accurately weigh compounds T5-T, T6-T, and T7-T, and place them separately into 5 mL brown volumetric flasks. Prepare solutions with spectrally pure tetrahydrofuran to a concentration of 1×10⁻⁶. -3 1. Use a mol / L standard solution as the stock solution; 2. Take 30 µL of the above stock solution using a microsyringe and dilute it to prepare a 1×10⁻⁶ solution. -5 The test solution is mol / L.

[0138] Sample preparation: Solid powders of compounds T5-T, T6-T, and T7-T

[0139] The maximum emission peaks of compound T5-T in solution and solid states are at 474 nm and 511 nm, respectively. This is compared with the fluorescence spectra of the room-temperature solution state. Figure 8 a) The solid-state spectrum exhibits a redshift, mainly attributed to the more compact molecular packing of the compound in the solid state. Furthermore, compound T5-T did not undergo aggregation-induced quenching in the solid state. Compounds T6-T and T7-T also exhibit similar properties in the solid state. Figure 8 (b, c). The luminescence lifetimes of compounds T5-T, T6-T, and T7-T in the solid state were characterized, with lifetimes of 7.6 μs, 1.6 ms, and 1.8 ms, respectively.

[0140] III. AIE Performance Characterization and Results Discussion

[0141] Instrument used: Fluorescence spectrometer (Hitachi F-7000)

[0142] To investigate the changes in luminescence behavior of compounds from the solution state to the aggregated state, compounds T5-T, T6-T, and T7-T were dissolved in the good solvent THF to prepare a concentration of 1×10⁻⁶. -3 The mother liquor was prepared at a concentration of mol / L, and then further prepared into solutions with different water contents (0-95%) and a concentration of 1 × 10⁻⁶. -5 The luminescence behavior of compound T5-T was studied using a mol / L THF / H2O mixed solution. Figure 9 ), T6-T ( Figure 10 ), T7-T ( Figure 11 It exhibits obvious AIE properties, respectively, at water content f w The fluorescence intensity reaches its maximum at 80%, 90%, and 90%, respectively, and is related to f. w Compared to when the concentration was 0, the fluorescence intensity increased by approximately 5, 23, and 14 times, respectively. Meanwhile, SEM and DLS characterization results showed that compounds T5-T, T6-T, and T7-T exhibited significantly different fluorescence intensities at water content f0. w When the concentration is 80%, 90%, or 90%, it aggregates into irregular nanoparticles, exhibiting good AIE performance.

[0143] IV. Characterization and Discussion of Solvation Effect

[0144] Instruments used: Fluorescence spectrophotometer (F-7000), steady-state-transient fluorescence spectrometer (Edinburgh FLS-1000);

[0145] Solvents used: n-hexane (Hex), 1,4-dioxane, ethyl acetate (EtOAc), tetrahydrofuran (THF), dichloromethane (DCM), N,N-dimethylformamide (DMF).

[0146] Sample preparation: The sample concentration for testing fluorescence emission spectra is 1×10⁻⁶. -5 mol / L dilute solution;

[0147] Selection of excitation wavelength: The optimal absorption wavelength was selected by ultraviolet-visible absorption spectroscopy and used as the excitation wavelength of the compound: the excitation wavelength of compounds T5-T, T6-T and T7-T is 360 nm.

[0148] Relative fluorescence quantum yield: Ф = (n x / n s ) 2 ·A s / A x ·D x / D s ·Фs (n: refractive index of the solvent, D: fluorescence emission area, A: absorbance, Ф) s Fluorescence quantum yield of standard substances, with quinine sulfate as the standard substance, Ф s = 0.54).

[0149] Thiophene in T5-T, T6-T, and T7-T exhibits a strong electron-donating effect, while cyano groups, as classic strong electron-withdrawing groups, are often used as electron acceptors to couple with electron donors to form DA systems, broadening the spectral range and improving quantum yield. Fluorescence emission spectra are as follows... Figure 12 As shown in (ac), the fluorescence emission peak position undergoes a slight redshift with increasing solvent polarity, but the fluorescence lifetime and quantum yield improve. This may be because polar solvents and excited-state molecules exhibit dipole interactions; changing the solvent polarity affects molecular emission. When solvent polarity increases, molecules with a DA structure undergo intramolecular charge transfer (ICT) effects, leading to luminescence. However, the twisted configuration of helene increases the molecular cross-sectional area, thus hindering the contact between polar solvent molecules and the cyano-helene conjugated core, reducing ICT, and ultimately resulting in a weak solvation effect. Despite the weak ICT and lack of a significant solvation effect, polar solvents can still reduce non-radiative decay by increasing the band gap, suppressing molecular motion, or stabilizing excited states, thereby improving the compound's fluorescence lifetime and quantum yield (see Table 1).

[0150] Table 1. Fluorescence quantum yield and fluorescence lifetime of compounds T5-T, T6-T, and T7-T in different solvents.

[0151]

[0152] Note: Ф F (Fluorescence quantum yield); τ (fluorescence lifetime)

[0153] V. Study on supramolecular gel behavior

[0154] The formation of organic supramolecular gels is mainly driven by intermolecular forces, while the presence of long-chain alkyl groups in the molecular structure enhances their gelation ability. This is attributed to the hydrophobic effect of the alkyl chains and their guiding role in molecular arrangement. Screening of the above assembly conditions demonstrated that compounds T5-T and T6-T gradually exhibited assembly behavior in decane with increasing concentration. Therefore, to further investigate the self-assembly behavior of the compounds in different solvents, this application examined their gel formation in various organic solvents, as shown in Table 2. During the experiment, quantitative samples were thoroughly mixed with solvents and heated to dissolution equilibrium, followed by gradient cooling to induce self-assembly. Gelation was determined by the absence of flowing solvent when the test tube was inverted. To measure the critical gel concentration, solvent was further added to the gel sample, and the critical gel concentration (CGC) was determined until this concentration was insufficient to form a stable gel after heating-cooling cycles. The study found that all three compounds exhibited a solution state in most solvents. Figure 13 Only T5-T and T6-T can form supramolecular gels in decane. Figure 14 (Illustration) Their critical gelation concentrations were 5.3 mg / mL and 5.0 mg / mL, respectively, while no such behavior was observed in other compounds (Table 2). The CGC of compound T6-T in decane was lower than that of T5-T, possibly due to better molecular arrangement during T6-T's self-assembly. To verify gel formation, the formation of a three-dimensional network structure was observed using scanning electron microscopy (SEM). Figure 14 This three-dimensional cross-linked network effectively binds liquid phase components through intermolecular interactions, suppressing solvent molecule diffusion and thus achieving a reversible transition from the sol system to the gel state. Furthermore, this application also characterized the morphology of compound T7-T in decane and methylcyclohexane solvents, such as... Figure 15 In the solvent system described above, compound T7-T aggregates into random agglomerates. This zero-dimensional disordered assembly morphology is not conducive to the chiral expression and amplification of the system.

[0155] Table 2. Gel behavior of compounds T5-T, T6-T, and T7-T in different solvents.

[0156]

[0157] Notes: G - gel; I - insoluble; S - solution; P - precipitate

[0158] Furthermore, a comparison of fluorescence spectra in the monomeric and gel states revealed that ( Figure 16After gel formation, compounds T5-T and T6-T showed increased fluorescence quantum yields from 1% and 0.8% in the monomeric state to 12% and 5.2%, respectively, with fluorescence intensities increasing by 12-fold and 6.5-fold, respectively. The lifetimes of the compounds in both states were also characterized. Figure 17 The lifetimes in the monomeric state were found to be 2.1 ns and 1.7 ns, respectively, which increased to 13.2 μs and 12.5 μs after gel formation.

[0159] VI. Research on Liquid Crystal Phase Behavior

[0160] To systematically elucidate the multilevel assembly mechanism and phase characteristics of thiaspirene-based liquid crystal molecules, characterization techniques such as TGA, DSC, and POM were employed to reveal the regulatory mechanisms of sulfur atom-mediated non-covalent bond synergistic interactions on the formation and stability of the liquid crystal phase. Specifically, TGA data verified the excellent thermal stability of the material through the rigid core and flexible alkyl chain molecular design of thiaspirene, providing a foundation for the ordered assembly and application of the liquid crystal phase over a wide temperature range. DSC analysis, through the continuity of endothermic / exothermic peaks, clarified the reversible liquid crystal phase transition behavior during heating and cooling. Further analysis of WAXS data confirmed the formation of a long-range ordered mesoscopic structure through the topological locking effect of sulfur atoms. POM observations of typical liquid crystal textures visually demonstrated the orientational order and birefringence of thiaspirene liquid crystal molecules. Cross-validation of these characterization results indicates that compounds T5-T, T6-T, and T7-T form liquid crystal phase structures through multiple non-covalent bond synergistic interactions.

[0161] (1) TGA characterization

[0162] Thermal decomposition temperature (T) d Thermogravimetric analysis (TGA) is a key parameter for evaluating the heat resistance of compounds in practical applications. Therefore, the thermal stability of the compounds was characterized by thermogravimetric analysis (TGA). The TGA curves are shown below. Figure 18 As shown, the thermal decomposition temperatures (temperatures at which the mass fraction decreases by 5%) of compounds T5-T, T6-T, and T7-T are all above 300 °C, indicating that the compounds all possess good thermal stability, providing a research basis for subsequent phase transformation or thermal annealing.

[0163] (2) DSC characterization

[0164] First, the phase transition temperature of the compound was determined using DSC. The temperature was initially increased at 10 °C / min to 200 °C to eliminate thermal history. Figure 19 The red curve represents the second heating process, and the blue curve represents the second cooling process. The same batch of samples was tested three times to eliminate errors. Figure 19It is observed that compound T5-T exhibits two phase transition peaks at -32 ℃ and 102 ℃ during the second heating process, and two more at -40 ℃ and 60 ℃ during the cooling process. The dual phase transition peaks and reversibility are consistent with the characteristics of thermotropic liquid crystals. Compound T6-T exhibits two phase transition peaks at 63 ℃ and 200 ℃ during the second heating process, and two more at 47 ℃ and 201 ℃ during the cooling process. The dual phase transition peaks and reversibility are consistent with the characteristics of thermotropic liquid crystals. Compound T7-T exhibits two phase transition peaks at 1 ℃ and 126 ℃ during the second heating process, and two more at -40 ℃ and 60 ℃ during the cooling process. The dual phase transition peaks and reversibility are consistent with the characteristics of thermotropic liquid crystals. The phase transition behavior of the thiaspirolyl liquid crystal molecules T5-T, T6-T, and T7-T conforms to the typical rules of thermotropic liquid crystals.

[0165] (3) POM characterization

[0166] Based on the above analysis, the liquid crystal texture of compounds T5-T, T6-T, and T7-T was observed using POM (Polymer Optical Microscope). A small sample of liquid crystal molecules was placed on a glass slide, covered with a coverslip, and the liquid crystal texture of the compounds was recorded using a heated stage and a polarizing microscope equipped with a digital camera. Compound T5-T showed birefringent crystals at 60 °C; upon further heating to 105 °C, it appeared completely black under the microscope's dark field; and as the temperature decreased to 80 °C, a filamentous liquid crystal texture was observed. Figure 20 This is a typical nematic phase texture. Compound T6-T exhibits birefringent crystals at 63 °C, but upon further heating to 110 °C, it appears completely black under a dark-field microscope. As the temperature decreases to 85 °C, a rectangular phase liquid crystal texture is observed. Figure 21 This is a smectic texture. Compound T7-T exhibits birefringent crystals at 65 °C; upon further heating to 140 °C, it appears completely black under a dark-field microscope; and as the temperature decreases to 95 °C, a mosaic liquid crystal texture is observed. Figure 22 This is a typical smectic texture.

[0167] VII. Study on Circularly Polarized Luminescence Properties

[0168] The three helene-based liquid crystal molecules T5-T, T6-T, and T7-T synthesized in this paper were not chiralized. The symmetry breaking during their assembly process and the CPL properties were studied by CD and CPL spectroscopy. Among them, compounds T5-T and T6-T can achieve chiral control in different solvent systems and phases.

[0169] (1) Study on the circularly polarized luminescence properties of the assembly

[0170] Compounds T5-T and T6-T can assemble into supramolecular gels in decane solvent, but their chirality cannot be regulated in a single solvent system. After multiple attempts, it was found that compounds T5-T and T6-T can undergo CD signal inversion in a chloroform / decane system, while compound T7-T does not show a CD signal. Figure 23 ).

[0171] Next, this application characterized the CPL of the T5-T and T6-T assemblies. Figure 24 The T5-T assembly exhibited a negative signal in the chloroform / decane (v / v = 6 / 4) solvent system, with an asymmetry factor of -0.6 × 10⁻⁶. -3 When the solvent ratio reaches chloroform / decane (v / v = 2 / 8), the CPL signal inverts and displays a positive signal with an asymmetry factor of 1.3 × 10⁻⁶. -3 The T6-T assembly showed a positive signal in a chloroform / decane (v / v = 3 / 7) solvent system with an asymmetry factor of 3.1 × 10⁻⁶. −3 When the solvent ratio reaches chloroform / decane (v / v = 7 / 3), the CPL signal inverts and displays a negative signal with an asymmetry factor of -2.2 × 10⁻⁶. -3 .

[0172] (2) Study on the circularly polarized light emission properties of liquid crystal phase

[0173] Compounds T5-T, T6-T, and T7-T were heated to isotropic conditions, and by controlling the cooling rate at 60 °C / min and 1 °C / min, respectively, liquid crystal phases and crystalline films that could exist stably at room temperature were obtained. T5-T and T6-T exhibited the Cotton effect in both phases; notably, they displayed opposite CD signals. Figure 25 The absence of a CD signal in compound T7-T may be due to the high inversion barrier of the helicene portion, which prevented configuration inversion. The equal proportion of enantiomeric components in its film resulted in macroscopic chiral cancellation.

[0174] Next, the CPL of T5-T and T6-T in different phase states was characterized. Figure 26 The liquid crystal phase film exhibits a positive CPL signal with an asymmetry factor of 2.3 × 10⁻⁶. -2 and 5.1×10 -2 However, it exhibits a negative signal in crystalline thin films, with an asymmetry factor of -3.6 × 10⁻⁶. -3 and -8.1 × 10 -3 It is speculated that this CPL signal inversion is due to the different molecular packing patterns of thiaspirene liquid crystal molecules in different phase states.

[0175] The results show that the introduction of sulfur atoms in compounds T5-T and T6-T enhances the intermolecular interactions, achieving symmetry breaking and chiral modulation in different solvent systems and phases. This is further demonstrated by the interaction with the g-phase assemblies in solution. lum Value comparison revealed that the liquid crystal phase g lum The value represents an order-of-magnitude increase. Compound T7-T, due to the large inversion energy barrier of the helicene moiety, failed to achieve symmetry breaking resulting from the configurational transition under current conditions, and thus failed to achieve CPL emission.

Claims

1. A class of thiaspirene compounds, characterized in that, The structure is as follows: 、 、 。 2. The method for synthesizing the thiaspirene compound according to claim 1, characterized in that, The synthesis route is as follows: , The specific preparation process is as follows: (1) Under a protective atmosphere, compound 5 and compound 6, 9 or 14 were dissolved in methanol to obtain a substrate solution, potassium tert-butoxide was dissolved in methanol to obtain a methanol solution of potassium tert-butoxide, the methanol solution of potassium tert-butoxide was cooled to -5~5℃, and the substrate solution was added dropwise to the methanol solution of potassium tert-butoxide under anaerobic conditions at -5~5℃, and the reaction was carried out at -5~5℃ for 20~40 min, then allowed to return to room temperature naturally, and then heated to 85~95℃ to complete the reaction; the reaction system was cooled to room temperature, methanol was removed by rotary evaporation, dichloromethane was extracted, the organic phases were combined, washed with water, dried, filtered, concentrated to obtain crude product, and compound 5a, 6a or 7a was obtained by washing with methanol and centrifugation. (2) Under a protective atmosphere, compound 5a, 6a or 7a was dissolved in dry toluene. After stirring and dissolving, iodine and propylene oxide were added. The reaction was irradiated with a high-pressure mercury lamp until complete. The reaction was quenched by adding saturated sodium sulfite solution, extracted with dichloromethane, the organic phases were combined, washed with water, dried and filtered, and concentrated to obtain crude product. Compound 5b, 6b or 7b was obtained by column chromatography. (3) Under a protective atmosphere, compounds 5b, 6b or 7b were dissolved in anhydrous diethyl ether and cooled to -70 to -80°C. Diisopropylaminolithium was added dropwise and the reaction was maintained at -70 to -80°C for 1 to 3 hours. DMF was added dropwise at -70 to -80°C. After the addition was completed, the temperature was naturally restored to room temperature and the reaction was complete. Methanol was added dropwise to the reaction system at -70 to -80°C to quench the reaction. DMF was removed by rotary evaporation. The system was extracted with dichloromethane. The organic phases were combined, washed with water, dried, filtered, and concentrated to obtain the crude product. Compounds 5c, 6c or 7c were obtained by column chromatography. (4) Dissolve compounds 5c, 6c or 7c, compound 19, and sodium ethoxide in a mixed solvent of ethanol and tetrahydrofuran, install a reflux condenser, and react completely at 45~55℃. Remove the solvent by rotary evaporation, extract with dichloromethane, combine the organic phases, wash with water, dry, filter, remove the solvent to obtain the crude product, and separate by column chromatography to obtain the target compounds T5-T, T6-T or T7-T.

3. The synthesis method according to claim 2, characterized in that, In step (1), the molar ratio of compound 6, 9 or 14, compound 5 and potassium tert-butoxide is (1.0~1.5):1:(1.5~2).

4. The synthesis method according to claim 2, characterized in that, In step (2), the molar ratio of compound 5a, 6a or 7a to elemental iodine and propylene oxide is 1:(1.5~2):(90~110), and the power of the high-pressure mercury lamp is 1000W.

5. The synthesis method according to claim 2, characterized in that, In step (3), the molar ratio of compound 5b, 6b or 7b, lithium diisopropylamino and DMF is 1: (1.1~1.5):

2.

6. The synthesis method according to claim 2, characterized in that, In step (4), the molar ratio of compound 5c, 6c or 7c, compound 19 and sodium ethoxide is 1:5:8, and the volume ratio of ethanol to tetrahydrofuran in the mixed solvent of ethanol and tetrahydrofuran is 3:

1.

7. The application of the thiaspirene compound of claim 1 as a liquid crystal material or a circularly polarized light-emitting material.